Putting the individual and context back into national human resource development research: A systematic review and research agenda. (28th July 2022) - Garavan, Thomas; Wang, Jia; Nolan, Ciara; Lai, Yanqing; O'Brien, Fergal; Darcy, Colette; Matthews‐Smith, Gerri; McLean, Gary
Abstract: Conceptualization of national human resource development (NHRD) emphasizes that it is an ongoing development process of the individual that is shaped by context. However, the extant literature has focused primarily on describing and evaluating NHRD policies and interventions in different countries with limited consideration of NHRD across the lifespan and the interaction of life stage with context. Using ecological systems theory (EST) and a lifespan development perspective (LDP), we present a systematic review of the NHRD literature based on 310 sources. We identify key themes and gaps in research across the lifespan and at distinct levels of the ecological system. We build on this review to suggest future research informed by both EST and an LDP. We propose a future research agenda focused on several key areas, including: the developing individual as the primary focus of NHRD; the dynamic relationship between NHRD microsystems and how this evolves over time; the exosystem and macrosystem, which provide the context of the NHRD development experience for the individual over their lifespan; and the imperatives of directing research attention to top‐down and bottom‐up influences within the ecological system. We also propose three methodological innovations to address many of the questions raised by our review, drawing on national archive databases, the use of historical methods and a focus on longitudinal data analysis. Finally, we highlight the practical implications of our analysis for ecosystem and microsystem NHRD actors.